Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 9204 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Peromyscus melanotis J.A.Allen & Chapman, 1897" ] } The dataset includes 9204 records from 43 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004253-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences